THE IMPACT OF CELEBRITY ENDORSEMENT AND SALES PROMOTION ON GENERATION Y’S ONLINE FASHION IMPULSIVE BUYING IN MANADO - Nadine Naomi Yovanca Kambey; James D. D. Massie; Regina Trifena Saerang (Universitas Sam Ratulangi, 2024)
The majority of companies have been using internet to conduct their services online especially on social media. This phenomenon trigger consumers to do unplanned purchase which called impulsive buying. Generation Y has been identified as materialistic, oriented toward brands, risk-takers and inclined toward business hedonism. This study aims to examine the impact of celebrity endorsement and sales promotion toward generation y’s online fashion impulsive buying. The survey was conducted through questionnaire with the sample of 100 respondents (generation y who have the experience in purchasing fashion items on online shop especially on social media). Data have been analyzed using SPSS 24. Results revealed that celebrity endorsement (celebrity trustworthiness, attractiveness, expertise) and sales promotion (on sale, bold sale price on product, additional purchase percent off, coupon, gift with purchase, free shipping or shipping discount) have significant influence on generation Y’s online fashion impulsive buying in Manado. For companies not currently utilizing celebrity endorsement strategies, it is suggested to consider hiring an endorser to broaden their customer base. Furthermore, online shops are advised to enhance the frequency of sales promotions to enhance overall profitability. Keywords: Celebrity Endorsement, Sales Promotion, Impulsive Buying